PERBANDINGAN METODE EVALUASI USABILITY (STUDI KASUS : PENGGUNAAN PERANGKAT SMARTPHONE) - Andrie Pasca Hendradewa (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
Usability is a key factor that determine success of a product or interactive system, like smartphone. The increasing use of smartphone and its rapid technology development, requires usability evaluation method that is more accurate and effective to found usability problem, so it can be used for product improvement in development process. This study suggests a usability evaluation method that is most effective to identify problem in smartphone usage. Three usability evaluation methods that commonly used are compared in this study, including: think-aloud evaluation (TA), cognitive walkthrough (CW), and heuristic evaluation (HE). This study involved 15 smartphone users as participants and 16 usability experts who is also a smartphone users as evaluators. The results showed, among the three usability evaluation methods, heuristic evaluation (HE) has the highest effectiveness and severity methods, while cognitive walkthrough (CW) and think-aloud evaluation (TA) still has potential for further development.